Low income renters and housing supports - Michael Doolan; Barra Roantree; Rachel Slaymaker (The Economic and Social Research Institute (ESRI), 2022)
Rental affordability challenges for low-to-moderate-income groups have been well documented. Changes to housing supports in recent years, notably the rapid expansion of Housing Assistance Payment (HAP), aim to address affordability challenges for low-income households in the rental sector. Within this context, this report seeks to inform our understanding of the current system of housing supports for low-income renters in Ireland. The report examines tenure patterns and rental affordability. It reviews the range and design of housing supports available to low-income renters and examines how the localised operation of differential rent schemes, which determines supported tenants' contributions, affects the level of and variation in support received. With the increased reliance on the provision of indirect housing supports (through rental subsidies or supplementary income supports), it also examines the availability of accommodation for low-income renters within the private rental sector. Housing supports - by virtue of being means-tested - affect the financial incentives individuals have with regards to being in paid work or working an additional hour. This report uses SWITCH, which is the ESRI's tax and benefit microsimulation model, to analyse the impact of these supports on the effective tax rates faced by low-income renters: a key consideration for any means-tested supports.
Keywords: 330; Soziale Wohnungspolitik; Öffentliche Sozialleistungen; Niedrigeinkommen; Mietwohnung; Irland